رثإ الأندلس بين نزار قباني وعبد العزيز درامان - Hishomudin Ahmad; Manjid Mustafa Bahjad (Hassiba Benbouali University of Chlef, Algeria, 2024)
The loss of Andalusia has had a great impact on the Muslim world. This tragedy is portrayed by countless Muslim poets throughout the centuries. Malay poets also shared the loss, indicating their interaction with the Islamic civilization in various dimensions, including: cultural and literary. However, their poems has not studied thoroughly. Therefore, this paper will compare two poetic texts on the loss of Andalusia by Nizar Qabbani and Abdul Aziz Deraman. The study relies on two main methods, inductive and analytical by comparing two texts, namely Granada by Nizar and Alhambra by Abdul Aziz. The findings show that Nizar mourned the loss of Andalusia from the perspective of Arab sentiment more than Abdul Aziz, who focused on the lessons that ought to be learnt from the tragedy. In addition the two poems strong structure, expression and composition, imagination and literary images, and rhythm.